Host and viral features of human dengue cases shape the population of infected and infectious Aedes aegypti mosquitoes. - Nguyet, M; Duong, T; Trung, V; Nguyen, T; Tran, C; Long, V; Dui, LT; Nguyen, H; Farrar, J; Holmes, E; Rabaa, M; Bryant, J; et al. (2013)
Dengue is the most prevalent arboviral disease of humans. The host and virus variables associated with dengue virus (DENV) transmission from symptomatic dengue cases (n = 208) to Aedes aegypti mosquitoes during 407 independent exposure events was defined. The 50% mosquito infectious dose for each of DENV-1-4 ranged from 6.29 to 7.52 log10 RNA copies/mL of plasma. Increasing day of illness, declining viremia, and rising antibody titers were independently associated with reduced risk of DENV transmission. High early DENV plasma viremia levels in patients were a marker of the duration of human infectiousness, and blood meals containing high concentrations of DENV were positively associated with the prevalence of infectious mosquitoes 14 d after blood feeding. Ambulatory dengue cases had lower viremia levels compared with hospitalized dengue cases but nonetheless at levels predicted to be infectious to mosquitoes. These data define serotype-specific viremia levels that vaccines or drugs must inhibit to prevent DENV transmission.